Dataset associated with "Device Characterization on Energy Design and Scoping Tool for DC Distribution Systems and a Study on Harmonics in AC/DC Converters in Low Voltage Distribution" and "Efficiency of AC vs. DC Distribution Systems in Commercial Buildings” - Santos, Arthur (Colorado State University. Libraries, 2020)
DC appliances have resurged with the evolution of power electronics and their massive application in Miscellaneous Electric Loads. The increase of DC distributed generation and battery storage also helped boosting the scientific community's attention to this other alternative. This work collects consumption data from appliances and converters connected to an AC distribution. The appliances that are focused in this study are also called Miscellaneous Electric Loads (MELs), which comprise all electronic loads in a building that are not related to lighting, heating, and air conditioning. Harmonics for these devices are analyzed, as this is part of a relevant project funded by the Department of Energy of the United States: the Energy Design and Scoping Tool for DC Distribution Systems. This work also presents results from another study, still within the scope of the same project, which aims to collect power consumption over a period of approximately two months of appliances commonly found in an office environment (laptop, screens, desktops, phone chargers and network devices). The data provided by this experiment will give a real estimate of these appliances' AC/DC converters operating range regarding their rated power. This will allow a more complete analysis to be carried out regarding the emission of harmonics in the power system and also a comparison between harmonic cancellation that is more likely to be occurring in low voltage distribution systems compared to the total cancellation potential.
AC appliances and converters were characterized in this study, having their current and voltage waveforms recorded at 15.36kHz. Harmonic analysis up to 7.68kHz is made, based on the data collected. Additionally, converters were loaded from 0% to 100% of their rated power, so their efficiency curve could be built. All this data is part of this dataset, and was collected during the years of 2019-2020, as one of the goals of the Energy Design and Scoping Tool for DC Distribution Systems project.
Department of Electrical and Computer Engineering
Keywords: harmonics; device characterization; DC distribution systems; DC design tool; energy design and scoping tool for DC distribution systems; converters characterization